Effect of diabetes type on long‐term outcome of epidermal axon regeneration. Issue 10 (27th September 2019) - Khoshnoodi, Mohammad; Truelove, Shaun; Polydefkis, Michael
Abstract: Objective: To assess the effect of diabetes type on the long‐term rate and extent of epidermal nerve regeneration. Methods: Subjects with well controlled type 1 diabetes mellitus ( n = 11) or type 2 diabetes mellitus ( n = 36), with normal nerve conduction studies and baseline intraepidermal nerve fiber density (IENFD), and healthy controls ( n = 10) underwent chemical axotomy of the intraepidermal nerves at the thigh using topical capsaicin. Skin biopsies were performed at 30, 90, 150, and 180 days post‐axotomy. Results: After 180 days, IENFD in diabetic subjects remained significantly below baseline levels, while healthy controls returned to normal. At each time point, regeneration rates were significantly slower among diabetic subjects, although type 1 subjects regenerated significantly faster and achieved higher percentages of baseline IENFD compared with type 2. Interpretation: Among diabetic patients, nerve injury recovery is likely to take significantly longer than in healthy individuals, and remains incomplete, particularly among type 2 patients. This may partially explain the progression of neuropathy among diabetic patients: damage accumulates because nerve recovery is slowed and incomplete. Furthermore, these findings support caution when recommending certain procedures, such as carpal tunnel repair, to patients with progressed diabetic disease.